A Prototype for Interactive Information Visualization as Support for Computer-Aided Diagnosis - Alvim, Larissa Terto; Gonçalves, Vagner Mendonça; Ribeiro, Matheus A. O.; Nunes, Fátima L. S. (Anais Estendidos do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS), 2025)
Computer-Aided Diagnosis (CAD) can offer a second opinion to help physicians compose a more precise diagnosis, and interactive Information Visualization (IV) tools can complement CAD systems by providing a more intuitive way to interpret data from patients and exams. In this study, we developed an interactive IV prototype to improve comprehension of a flexible database for a CAD system in the cardiomyopathies context. This prototype is integrated with a web application to retrieve Cardiac Magnetic Resonance exams, and a qualitative evaluation conducted with health professionals showed that IV provided valuable data analysis capability. The results have shown that the integration of advanced visualization tools in our developed prototype can enhance clinical decision-making, improving the effectiveness of CAD systems.